In situ growth of M-MO (M = Ni, Co) in 3D graphene as a competent bifunctional electrocatalyst for OER and HER. (1st March 2019) - Ullah, Nabi; Zhao, Wentong; Lu, Xiaoqing; Oluigbo, Chidinma Judith; Shah, Sayyar Ali; Zhang, Mingmei; Xie, Jimin; Xu, Yuanguo
Abstract: In this study, an efficient and cheap electrocatalysts are prepared by a simple synthetic method for oxygen evolution reaction (OER) hydrogen evolution reaction (HER). Nickel/nickel oxide@3dimensional hierarchical porous graphene (Ni-NiO@3DHPG) and cobalt/cobalt oxide@3dimensional hierarchical porous graphene (Co-CoO@3DHPG) electrocatalysts were obtained from cation exchange resin, nickel acetate and cobalt nitrate as a source of carbon, Ni and Co respectively. In Ni-NiO@3DHPG and Co-CoO@3DHPG, metal and metal oxide nanoparticles embedded in the graphene layers, were confirmed by different techniques. The 3-D graphene in Ni-NiO@3DHPG and Co-CoO@3DHPG were thinned wall and highly porous structure and large specific surface area. The Ni-NiO@3DHPG composite displays onset potential, overpotential (10 mA cm −2 ) and Tafel value of are 1.53 V, 1.64 V and 55 mV dec −1 for OER and −0.18 V, −0.31 V and 78 mV dec −1 for HER respectively. Similarly, Co-CoO@3DHPG catalyst show onset potential, overpotential (10 mA cm −2 ) and Tafel are 1.59 V, 1.68 V and 65 mV dec −1 for OER and −0.26 V, −0.40 V and 85 mV dec −1 for HER respectively. Electrocatalysts show good stability after 4 h continuously. This simple synthetic method will open a new way for cheap and efficient electrocatalysts of other types of non-precious metals for OER and HER. Graphical abstract: A simple method was used to in situ grown Ni-NiO and Co-CoO in three dimensional hierarchical porous graphene by ion exchange/activation method. The obtained Ni-NiO@3DHPG and Co-CoO@3DHPG show efficient performance for OER and HER. the better performance of Ni-NiO@3DHPG and Co-CoO@3DHPG are due to well dispersion of Ni-NiO and Co-CoO particle in graphene layers and high conductivity of graphene layer which facilitate fast transport of electron. Highlights: - A novel and less toxic alternative precursor to synthesize 3DHPG. Ni-NiO@3DHPG and Co-CoO@3DHPG active and stable electrocatalyst for OER and HER. The efficient activities attributed to Ni-NiO and Co-CoO and condutive graphene.